SPATIAL MAPPING OF ENVIRONMENTAL SENSITIVE INDEX IN PULAU HUJUNG AND PULAU TENGAH, JOHOR - Asmawi, M. Zainora; Mohd Daud, Muhammad Adil Ramzi; Abd Aziz, Abdul Razak (Journal of Architecture, Planning and Construction Management, 2020)
This paper addresses the necessity of sea spatial mapping for valuable natural resources of the island ecosystem in Pulau Hujung and Pulau Tengah, Johor. These islands are located in Johor Marine Park, rich with a diversity of marine life, resources, valuable ecosystems, and historical and cultural values. As an environmental asset considered as Environmental Sensitive Areas (ESA), the spatial mapping of its different zonal uses by using the Environmental Sensitive Index (ESI) is crucial in planning and managing natural resources within protected areas. By integrating the data of ESAs into the GIS application via the ESI, the generation of its outcome of digital mapping is easier to understand and applicable in managing the planning of the islands. The indices of ESI comprise of biological and human resources, and shoreline classification. Besides, the research refers to international guidance, namely the IUCN Guideline 2008 where the requirements of ESA protection were clearly stated. The results of the spatial mapping demonstrate that the islands could be categorised as preservation zone, habitat protection zone, general use zone, and buffer zone, in which each of these sea zonal use reflects both its characteristics and importance. The division of clear zones helps the relevant authorities to manage and monitor this special area so that these natural resources, marine life, and ecosystems can be sustained as the natural heritage of the nation. In a conclusion, it is evident that the spatial sea zonal use map is very significant and may benefit many stakeholders involved in planning and managing the waters of the eastern part of Johor.